The Figure of Maryam in the Narrative of Revelation: A Historical and Cultural Study of the Role of Women in Global Islamic Civilization - Pamungkas, Achmad Firman; Husnina, Kanza; Mubarokah, Nur Lailiyatul; Faizah, Nur Laila Hidayatul (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study examines the figure of Maryam, the mother of Prophet Isa, as portrayed in the narrative of revelation in the Qur’an and Hadith, through a historical and cultural approach focusing on her role in global Islamic civilization. Maryam is the only woman explicitly named in the Qur’an, with a profound story that extends beyond theological dimensions to encompass social, cultural, and even interfaith aspects. The aim of this research is to explore how Maryam is positioned as a symbol of purity, steadfast faith, and female strength within the construction of Islamic civilization, and how this representation is understood in cross-cultural and global contexts—especially in today’s era of uncertainty.The methodology used is historical, following the stages of heuristics, verification, interpretation, and historiography, complemented by a role-based approach to identify and analyze the social and symbolic functions of Maryam in the history of the Muslim community. Primary sources analyzed include Qur’anic verses, authentic Hadith, and both classical and contemporary tafsir literature. The findings reveal that Maryam serves not only as a spiritual figure but also as a cross-cultural icon who enriches interfaith dialogue and becomes a source of inspiration in discourses on gender equality and universal human values.